Poverty trends during two recessions and two recoveries: Lessons from Sweden 1991-2013 - Jan O. Jonsson; Carina Mood; Erik Bihagen (IZA Journal of European Labor Studies, 2016)
We study cross-sectional and long-term poverty in Sweden over a period spanning two recessions, and discuss changes in the policy context. We find large increases in absolute poverty and deprivation during the 1990's recession but much smaller increases in 2008-2010. While increases in non-employment contributed to increasing poverty in the 1990's, the temporary poverty increase 2008-2010 was entirely due to growing poverty among non-employed. Relative poverty has increased with little variation across business cycles. Outflow from poverty and long-term poverty respond quickly to macro-economic recovery, but around one percent of the working-aged are quite resistant to such improvements.
Keywords: I30; I32; E32; 330; Poverty; Recessions; Income inequality; Sweden; Long-term poverty; Material deprivation